Lively accounting / Norliana Omar ... [et al.] - Omar, Norliana; Osman, Amir Hakim; Mohd Isa, Noor Saatila; Khair Anwar, Irda Syahira; Mohd Suffian, Mohd Taufik (2020)
Lively accounting is a flashcard with interactive video provides a revolutionary new way of quickly and easily understanding of financial accounting. Learning with lively flashcards are an incredibly versatile study tool because it enhances self-learning activities for students to remember a term, concept or process. Students today are utilizing educational videos as a tool for learning everything. As a result, educational institutions are faced with the task of meeting the rising demand for quality learning videos. Studies have shown that the use of short video clips allows for more efficient processing and memory recall. Hence, simple survey has been conducted, asking for students' opinion regarding other preferable tools to help them in online learning. The results showed that students demand for videos with audios to further explain the subject matter. Educational institutions can gain great autonomy by using videos to reach their broad audience. Therefore, development of lively flashcards with interactive video believe to be acceptable since it is more effective, faster and easier to use as compared to the wordy accounting standards or printed handouts. Furthermore, lively flashcards are accessible at the student convenience and the video can be watch numerous times to assist with coursework and skill mastery.